The Enactment of the Common Interest Concept and the Theory of Repressive Legal Protection on Consumer Reviews Against Defamation Claims - Evi Kongres; Kevin Kogin; Connie Susilawati (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2024)
Essentially, the objective of reviews is to offer testimonials regarding the quality of product based on personal experiences, serving as a reference for potential consumers concerning the product’s attributes and quality. Businesses also leverage consumer reviews as material for product evaluation, marketing, and enhancing after-sales services. However, in practice businesses do not always receive consumer reviews favorably, particularly when these reviews result in financial losses. This is especially true when reviews are published by influencers with substantial social media followings. Consequently, businesses may initiate legal action against consumers for defamation. According to defamation provisions, acts carried out in the public interest cannot be penalized. This study addresses the legal protection of consumers against defamation lawsuits by businesses, employing the common interest concept and the theory of repressive legal protection. The aim is to analyze the application of the common interest concept and the theory of repressive legal protection concerning reviews on social media, aiming to provide new insights for law enforcement officials in handling defamation cases involving consumers and businesses. This study utilizes normative juridical methods, reviewing literature on legislation, legal concepts, and theories. The study concludes that according to the theory of repressive legal protection, businesses that violate their obligations to consumers should be sanctioned. The enactment of the common interest concept to consumer reviews requires an examination of legal evidence and facts, and if proven, should result in sanctions for businesses as a form of repressive legal protection.